2013
DOI: 10.5301/hip.2013.10613
|View full text |Cite
|
Sign up to set email alerts
|

The Analgesic Impact of Preoperative Lumbar Plexus Blocks for Hip Arthroscopy. A Retrospective Review

Abstract: This study aimed to examine the impact of preoperative lumbar plexus blockade on perioperative analgesia and opioid consumption following hip arthroscopy. The records of patients (n = 236) who underwent hip arthroscopy between July 27, 2004 and November 15, 2009 were reviewed (118 patients with preoperative lumbar plexus block and 118 procedure matched patients without a preoperative block). Baseline patient characteristics were similar between groups. Immediate post-anaesthesia care unit (PACU) pain scores, p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
40
0

Year Published

2014
2014
2019
2019

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 34 publications
(40 citation statements)
references
References 18 publications
0
40
0
Order By: Relevance
“…Schroeder et al [21] determined the effect of an LBP versus general anesthesia in a retrospective series of 236 patients. Lumbar plexus blocks were performed in a room dedicated to regional anesthesia techniques.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Schroeder et al [21] determined the effect of an LBP versus general anesthesia in a retrospective series of 236 patients. Lumbar plexus blocks were performed in a room dedicated to regional anesthesia techniques.…”
Section: Resultsmentioning
confidence: 99%
“…In the study of YaDeau et al [17], LPB significantly reduced pain scores in the PACU, it is questionable if this difference is clinically relevant since pain scores were similar in both groups 4 h after surgery. Schroeder et al [21] reported in their retrospective review significantly lower immediate and peak PACU pain scores in the LPB group. Unfortunately, no separate VAS scores were measured over a longer period of time.…”
Section: Discussionmentioning
confidence: 99%
“…For all 6 included studies, [16][17][18][27][28][29] data were collected regarding the study specifics, patients included, and outcomes measured in the study. The journal of publication, type of study, level of evidence, and type of PNB, as well as the presence of a comparator group were noted ( Table 2).…”
Section: Methodsmentioning
confidence: 99%
“…This significant difference did not persist at 24 hours or 6 months after the procedure, nor did it exist for pain with movement at any time point. Similarly, Schroeder and colleagues 17 examined patients receiving general anesthesia and lumbar plexus block and found a significant reduction in pain immediately postoperatively in the PACU, though these effects disappeared the day following the procedure. Krych and colleagues 27 also reported on postoperative pain in patients undergoing fascia iliaca blockade, although they did not include a comparator group.…”
Section: Postoperative Painmentioning
confidence: 96%
See 1 more Smart Citation